Cell Seeding Process Experiment and Simulation on Three-Dimensional Polyhedron and Cross-Link Design Scaffolds - Liu, Ziyu; Tamaddon, Maryam; Gu, Yingying; Yu, Jianshu; Xu, Nan; Gang, Fangli; Sun, Xiaodan; Liu, Chaozong (Frontiers in Bioengineering and Biotechnology, 2020)
Controlled cell seeding on scaffolds is a significant step towards successful tissue engineering. It is essential to know the cell seeding efficiency and distribution to be able to optimize the design of tissue engineering scaffolds. Two type of scaffolds, including truncated octahedron structure and cubic structure, were designed for vitro cell seeding investigation and subsequently modification for simulation approach. Both of scaffold showed a gradual lateral variation of attached cells, and live cells movement are exremly slow by only diffusion while dead cell can not move without external force. A simulation approach, by ANSYS Fluent coupling the VOF model, DPM model and CIM model, was developed for cell seeding process in scaffold. The simulation approches supply a more accurate model to simulate cells adhesion for three-dimension structure. As the initial stages of cell attachment in vivo are hard to observe, this novel method provides an opportunity to predict cells distribution, thereby helping to optimize scaffold structures. As tissue formation is highcly related to the cell distribution, this model may help researchers to predict the effect of applied scaffold and reduce the number of animal testing.